Предмет: Математика,
автор: Flokis
Решите уравнение 3(4 – 2х) + 6 = -2х + 4
Ответы
Автор ответа:
1
Ответ:
x=3.5
Пошаговое объяснение:
3(4 – 2х) + 6 = -2х + 4
12-6x+6+2x-4=0
-4x+14=0
-4x=-14
x=14/4
x=7/2
x=3.5
Flokis:
Уж такому профилю можно доверить)
Автор ответа:
0
Ответ:
Пошаговое объяснение:
12-6x+6=-2x+4
-4x=-14
x=3.5
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: катяhhh
Предмет: Русский язык,
автор: dimefremow
Предмет: Литература,
автор: Imzalupa
Предмет: Математика,
автор: русвлина